Efisiensi Pemasaran Kopi Arabika di Kabupaten Tana Toraja - Gabryaldo, Igods; Darma, Rahim; Mahyuddin, Mahyuddin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Most of the raw Arabica coffee in Tana Toraja Regency is marketed in the form of Horn Skin (HS) coffee. This study aims to analyze the marketing efficiency of raw Arabica coffee in Tana Toraja Regency. The research was conducted in Mengkendek and Gandangbatu Sillanan Districts using a snowball sampling method, while sample selection was carried out through purposive sampling. The samples in this study consisted of coffee processing industries, namely the Autonomous Business Unit (UUO) of Agribusiness Toraja and Gandangbatu Coffee, as well as marketing institutions involved in the distribution of raw Arabica coffee to these industries. Data were collected through surveys and analyzed using both qualitative and quantitative approaches, applying the Structure-Conduct-Performance (S-C-P) model as the analytical framework. The results indicate that the most efficient marketing system for raw Arabica coffee is the marketing system for cherry coffee. Although the market structure in this system tends to be monopsonistic, farmers still maintain strong bargaining power. This is due to the limited number of farmers who can sell cherry coffee, as it requires a high-quality standard. As a result, farmers receive higher prices. Additionally, farmers do not incur marketing costs, making the marketing margin and profit margin ratio in the cherry coffee marketing system equal to zero.